2016
DOI: 10.1002/hep.28695
|View full text |Cite
|
Sign up to set email alerts
|

A new 3p25 locus is associated with liver fibrosis progression in human immunodeficiency virus/hepatitis C virus‐coinfected patients

Abstract: This genome-wide association study identified a new locus associated with liver fibrosis severity in patients with HIV/HCV coinfection, on chromosome 3p25, a finding that was replicated in patients with HCV monoinfection; these results provide new relevant hypotheses for the pathogenesis of liver fibrosis in patients with HIV/HCV coinfection that may help define new targets for drug development or new prognostic tests, to improve patient care. (Hepatology 2016;64:1462-1472).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…To evaluate the pathological role of the expanded population of MkP in driving bone marrow fibrosis, we next examined potential mediators of fibrosis. Fibrosis regulators were identified from previously published datasets studying lung and liver fibrosis as well as bone marrow fibrosis (Allen et al, 2017;Blackman et al, 2013;Corvol et al, 2015;Gu et al, 2009;Mondet et al, 2015;Mushiroda et al, 2008;Noth et al, 2013;Ulveling et al, 2016;Wattacheril et al, 2017;Wright et al, 2011). Genes detected at expression levels over 1 (using log-transformed UMI) were selected for a 'fibrosis signature' gene score (Suppl.…”
Section: Identifying Mediators Of Megakaryocyte-induced Fibrosismentioning
confidence: 99%
“…To evaluate the pathological role of the expanded population of MkP in driving bone marrow fibrosis, we next examined potential mediators of fibrosis. Fibrosis regulators were identified from previously published datasets studying lung and liver fibrosis as well as bone marrow fibrosis (Allen et al, 2017;Blackman et al, 2013;Corvol et al, 2015;Gu et al, 2009;Mondet et al, 2015;Mushiroda et al, 2008;Noth et al, 2013;Ulveling et al, 2016;Wattacheril et al, 2017;Wright et al, 2011). Genes detected at expression levels over 1 (using log-transformed UMI) were selected for a 'fibrosis signature' gene score (Suppl.…”
Section: Identifying Mediators Of Megakaryocyte-induced Fibrosismentioning
confidence: 99%
“…A range of candidate gene and GWA studies of HIV-related traits have been reported, such as atherosclerosis (Shrestha et al 2010 ), response to antiretroviral drugs (Chantarangsu et al 2011 ; Irvin et al 2011 ; Leger et al 2014 ; Lehmann et al 2015 ), and blood counts in HIV-infected or -exposed patients (Ferreira et al 2010 ; Moore et al 2015 ; Ramsuran et al 2011 ). Similarly HIV-associated diseases have also been interrogated, such as HIV-dementia (Levine et al 2012 ) and hepatitis C (Ulveling et al 2016 ). Although we do not discuss each study in detail here, Supplementary Table 1 provides a recent extract from the GWAS catalog for all HIV and related traits.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs61183828 had a strong association with a genome‐wide level of significance, which was replicated in two independent cohorts of HCV‐mono‐infected patients. Interestingly, a cluster of SNPs in linkage disequilibrium with rs61183828 is located close to two genes involved in mechanisms affecting both cell signaling and cell structure ( CAV3 ) and HCV replication ( RAD18 ) …”
Section: Disease Progressionmentioning
confidence: 99%
“…Interestingly, a cluster of SNPs in linkage disequilibrium with rs61183828 is located close to two genes involved in mechanisms affecting both cell signaling and cell structure (CAV3) and HCV replication (RAD18). 21…”
Section: Disease Progressionmentioning
confidence: 99%